FLUOROMETRIC ASSAY FOR CELL PROLIFERATION IN HUMAN TUMOR CELL LINES APPLICATION - Escobar M., Linamaría; Aristizábal G., Fabio A. (Vitae, 2010)
Assessment of in vitro cytotoxicity as a model to explore biological activity of compounds isolated from different sources is the first approached to search molecules with potential anticancer activity. This paper is about how to implement resazurin reduction method as an indirect indicator of cell survival. Indeed both optimal resazurin concentration and incubation time were selected on MCF-7, MKN-45, SiHa, HEp-2, HT-29 and HeLa. Next, we compared survival results by using reduction method MTT and staining method SRB defined as end-point tests, and resazurin method described as slightly toxic to cells. The comparison of the methods was done in terms of survival rate to evaluate the sensitivity of the lines to doxorubicin HCl, a medicine used in cancer. The methods were compared in terms of percentage survival by evaluating cell line sensitivity to doxorubicin HCl (a drug used in cancer treatment). The results show that resazurin reduction method used in 4.4 μM is applicable to detect significant changes in cell population exposed to cytotoxic molecules in routine testing.